Analysis of harmonics currents in the case of grid connected photovoltaic generator - Assia, Habbati Bellia; Fatima, Moulay (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Nowadays, electrical grid experiences an increase in penetration of single-phase PV generations. Then, it becomes necessary to control this penetration by techniques of synchronization in order to provide electrical energy of good quality to the network. Estimation of the frequency, phase and magnitude of the grid voltage are necessary to correctly synchronizing the PV generator with grid. Connecting a direct current generator to grid via an inverter, requires to fix the performances to improve in the inverter to choose the best-suited topology. This paper describes the control of a non-isolated single-stage single-phase grid-connected inverter fed by a photovoltaic source. In order to define the influence of the three parameters: modulation index, switching frequency and phase shift angle, it is interesting to know the behavior of the system when one of these parameters moves away from its optimal value. Optimal values make it possible to obtain a THD as small as possible to satisfy the international standard. In this work, modulation index and switching frequency are set to their respective optimal values. To study grid current and inverter currents before and after filtering, harmonic analysis is performed for seven shift angles for the same switching frequency (10000 Hz) and modulation index (2.2).